EFEKTIVITAS KOMBINASI JUS HATI AYAM DAN SERBUK BIJI MELINJO SEBAGAI BAHAN PENGINDUKSI HIPERURISEMIA PADA TIKUS - Mawar Subangkit; Jurnila Sari Tanjung; Siti Sadiah (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2022)
An in vivo test study to prove its effectiveness as an antihyperuricemia requires an animal model with a hyperuricemic condition. Foods that contain high purine bases have the potential to increase uric acid levels in the blood, including chicken liver and melinjo seeds. This study aims to determine the effectiveness of the combination of chicken liver juice and melinjo seed powder in producing hyperuricemia conditions with the most optimal onset and duration in rats in vivo. Six groups of white Sprague Dawley rats (n=5) consisted of a normal group, a positive control group, a chicken liver juice group, a melinjo seed powder group and two groups that were given a combination of chicken liver juice and melinjo seed powder with different compositions. The treatment was given every day for 15 days orally. The parameters observed were uric acid levels which were measured every 3 days and, body weight. The results showed that the combination of chicken liver juice and melinjo powder with a half dose of a single dose each had a better onset and duration. The conclusion of this study is that the combination of chicken liver juice and melinjo seed powder is potent as an inducer of hyperuricemia in rats.